Development of RT-qPCR and semi-nested RT-PCR assays for molecular diagnosis of hantavirus pulmonary syndrome. - Bruno Tardelli Diniz Nunes; Maria Helena Rodrigues de Mendonça; Darlene de Brito Simith; Adriana Freitas Moraes; Carla Conceição Cardoso; Ivy Tsuya Essashika Prazeres; Ana Alice de Aquino; Alessandra da Conceição Miranda Santos; Alice Louize Nunes Queiroz; Daniela Sueli Guerreiro Rodrigues; Regis Bruni Andriolo; Elizabeth Salbé Travassos da Rosa; et al. (Public Library of Science (PLoS), 2019)
Hantavirus Pulmonary Syndrome is an, often fatal, emerging zoonotic disease in the Americas caused by hantaviruses (family: Hantaviridae). In Brazil, hantavirus routine diagnosis is based on serology (IgM-ELISA) while RT-PCR is often used to confirm acute infection. A Semi-nested RT-PCR and an internally controlled RT-qPCR assays were developed for detection and quantification of four hantaviruses strains circulating in the Brazilian Amazon: Anajatuba (ANAJV) and Castelo dos Sonhos (CASV) strains of Andes virus (ANDV) species; and Rio Mamoré (RIOMV) and Laguna Negra (LNV) strains of LNV species. A consensus region in the N gene of these hantaviruses was used to design the primer sets and a hydrolysis probe. In vitro transcribed RNA was diluted in standards with known concentration. MS2 bacteriophage RNA was detected together with hantavirus RNA as an exogenous control in a duplex reaction. RT-qPCR efficiency was around 100% and the limit of detection was 0.9 copies/μL of RNA for RT-qPCR and 10 copies/μL of RNA for Semi-nested RT-PCR. There was no amplification of either negative samples or samples positive to other pathogens. To assess the protocol for clinical sensitivity, specificity and general accuracy values, both assays were used to test two groups of samples: one comprising patients with disease (n = 50) and other containing samples from healthy individuals (n = 50), according to IgM-ELISA results. A third group of samples (n = 27) infected with other pathogens were tested for specificity analysis. RT-qPCR was more sensitive than semi-nested RT-PCR, being able to detect three samples undetected by conventional RT-PCR. RT-qPCR clinical sensitivity, specificity and general accuracy values were 92.5%, 100% and 97.63%, respectively. Thus, the assays developed in this study were able to detect the four Brazilian Amazon hantaviruses with good specificity and sensitivity, and may become powerful tools in diagnostic, surveillance and research applications of these and possibly other hantaviruses.